2010
DOI: 10.1523/jneurosci.4711-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dyrk1A Overexpression Inhibits Proliferation and Induces Premature Neuronal Differentiation of Neural Progenitor Cells

Abstract: Dyrk1A is a member of the mammalian Dyrk [dual-specificity tyrosine-(Y)-phosphorylation regulated kinase] family of protein kinasesthat is expressed at high levels in the brain, but its role in the development and function of this organ is not well understood. The human DYRK1A gene is located on trisomic chromosome 21 in Down syndrome (DS) patients, leading to its overexpression. Dyrk1A is also overexpressed in animal models of DS and in gene-specific transgenic mice that consistently exhibit cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
128
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 38 publications
(53 reference statements)
9
128
1
4
Order By: Relevance
“…S8). Our findings are in agreement with the study by Yabut et al (2010) and imply that levels of DYRK1A dosage influence downstream pathways differently.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…S8). Our findings are in agreement with the study by Yabut et al (2010) and imply that levels of DYRK1A dosage influence downstream pathways differently.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, a previous study has demonstrated that, in contrast to our study, DYRK1A electroporation in the mouse neocortex suppressed progenitor proliferation via misregulation of cell cycle regulators and leads to precocious neuronal differentiation that is not seen in DS model mice (Yabut et al 2010). Since expression levels of DYRK1A were not examined in progenitors in Yabut et al (2010), we presumed that a much higher dosage of DYRK1A might be expressed in their study, thereby causing a different phenotype.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…7I), but not other CDK inhibitors, including p27 KIP1 and p15 INK4B (data not shown). Similar to our finding, Yabut et al also reported very recently that transiently overexpressed Dyrk1A by in utero electroporation inhibits neural cell proliferation in embryonic mouse neocortex (41). Although more studies should be performed, the current finding indicates that Dyrk1A overexpression leads to impaired neuronal proliferation through the signaling pathway containing p53 and p21 CIP1 during late embryonic brain development.…”
Section: Discussionsupporting
confidence: 92%
“…Dyrk1A is also known to phosphorylate proteins associated with mRNA splicing (Cyclin L2, SF2, and SF3) and translation (eIF2B⑀) (42). Interestingly, Yabut et al recently reported that transiently overexpressed Dyrk1A by in utero electroporation inhibits neural cell proliferation in embryonic mouse neocortex, in which the nuclear export and degradation of cyclin D1 could act as a key cell cycle modulator (41). This study also supports our finding in several aspects.…”
Section: Discussionsupporting
confidence: 91%